Surgical Removal of Shaving Blade from Stomach of Dog - Mithilesh Kumar; Premlata Kumari; Ravi Ranjan Kumar; Arvind Kumar Singh (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 2 years old Labrador dog brought with history of ingestion of a newly paper covered packet shaving blade immediately falling from owner's hand during his shaving one day after the incident. There were no clinical signs observed and the dog was normal. Lateral radiography taken showed radio-opaque shaving blade in the stomach area. Solid food was not given after ingestion of shaving blade till surgical intervention and under general anaesthesia shaving blade was removed surgically. The stomach was sutured with vicryl no. 1/0 in continuous lumbert and cushing pattern in double layer. Post-operatively administration of antibiotics, analgesics and regular dressing of wound was done and dog recovered uneventfully.